A three-phase, multi-component ionic transport model for simulation of chloride penetration in concrete. (1st March 2015) - Liu, Qing-feng; Easterbrook, Dave; Yang, Jian; Li, Long-yuan
Highlights: This paper considers the interactions between ionic species to simulate the RCM test. This paper expands the previous 2-phase, multi-component transport model to a 3-phase one. This paper quantifies the opposite effects of binding and ITZ on multi-ionic migration. Abstract: Chloride-induced corrosion of reinforcing steel in concrete is a serious problem in the durability of structures. In order to predict how chlorides penetrate in concrete, unlike most existing models which consider the penetration of only a single species or in a single phase medium, this paper presents a numerical model considering the transport of multiple species in a multi-phase medium. The 2-D, 3-phase, multi-component ionic transport model proposed in the paper also considers ionic binding and the model is used to simulate the rapid chloride migration (RCM) test of concrete. The effects of aggregates, ITZs and ionic binding on chloride penetration in concrete are examined and discussed. The obtained result is also validated against experimental data obtained in an accelerated chloride migration test.